Eksplorasi Penggunaan Aktual Dompet Digital DANA dalam Transaksi Digital: Perspektif Technology Acceptance Model (TAM) - Maulana Ridho Pratomo; Hikmatun Nisa; Khansa Hanun; Ni’mal Mujahidah; Alvira Rizka; Joko Tri Nugraha (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study aims to analyze the influence of Perceived Ease of Use, Perceived Usefulness, and Behavioral Intention to Use on the Actual System Use of the DANA e-wallet application in digital transactions using the Technology Acceptance Model (TAM) framework. A quantitative associative approach was employed, with data collected through structured questionnaires distributed to active DANA users selected via purposive sampling, predominantly from the Gen Z demographic. Data were analyzed using multiple linear regression, classical assumption tests, and hypothesis testing. The findings reveal that Perceived Ease of Use and Perceived Usefulness do not significantly influence Actual System Use partially, while Behavioral Intention to Use demonstrates a dominant and significant effect. Simultaneously, all three variables significantly explain the majority of the variance in actual usage. These results suggest that among Gen Z users, trust and behavioral intention outweigh functional attributes such as ease of use and perceived usefulness in driving actual adoption of digital wallets. The study contributes theoretically to TAM-based digital payment research and practically recommends that DANA prioritize building user trust through enhanced security, data transparency, and digital literacy programs to sustain long-term adoption.